Student Responses and Effectiveness of Android Media as Chemistry Learning Media During the Covid-19 Pandemic - Noor Rifaan; Agung Tri Prasetya; Sri Susilogati; Woro Sumarni; Widhi Mahatmanthi (Jurnal Pendidikan Kimia Indonesia, 2022)
The Covid 19 pandemic has prevented learning from being carried out face-to-face but online using a smartphone. This study aims to analyze the effectiveness of android media as a chemistry learning medium during a pandemic. This type of research is qualitative research using the study of literature from scientific journals. The data analysis method used is descriptive qualitative. This systematic method uses PRISMA guidelines and flowcharts. Methods of data collection using non-test methods, namely observation and interviews. The analysis technique uses qualitative analysis. The study results of the response and effectiveness of Android media are used to consider using Android media as a suitable learning medium during a pandemic. The subject of the study was Sinta 1 to Sinta 6 accredited scientific journals between 2011 and 2021. This article limits the use of android media in high school chemistry learning. The results of scientific journal studies show that most students respond very well to the use of android media in chemistry learning. The effectiveness of using Android-based media for chemistry learning can increase student motivation, cognitive learning outcomes, problem-solving skills, critical thinking, scientific literacy, and student activity. The conclusion shows that Android media is suitable for use as a learning medium during a pandemic.